2010
DOI: 10.5812/asjsm.34853
|View full text |Cite
|
Sign up to set email alerts
|

Is Body Fat a Predictor of Race Time in Female Long-Distance Inline Skaters?

Abstract: Purpose: The aim of this study was to evaluate predictor variables of race time in female ultra-endurance inliners in the longest inline race in Europe. Methods:We investigated the association between anthropometric and training characteristics and race time for 16 female ultraendurance inline skaters, at the longest inline marathon in Europe, the 'Inline One-eleven' over 111 km in Switzerland, using bi-and multivariate analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…Another major predictor variable for a successful outcome in endurance competitions is the percentage of body fat [32]. Several studies investigated the correlation between the percentage of body fat and the performance of ultra-endurance athletes [33,34]. Knechtle et al [35,36] reported the average body fat percentage for female 100-km ultramarathoners at approximately 26.8% (20.0% to 31.4%) or approximately 17.0 kg and for men at approximately 16.1% equal to approximately 11.9 kg.…”
Section: Discussionmentioning
confidence: 99%
“…Another major predictor variable for a successful outcome in endurance competitions is the percentage of body fat [32]. Several studies investigated the correlation between the percentage of body fat and the performance of ultra-endurance athletes [33,34]. Knechtle et al [35,36] reported the average body fat percentage for female 100-km ultramarathoners at approximately 26.8% (20.0% to 31.4%) or approximately 17.0 kg and for men at approximately 16.1% equal to approximately 11.9 kg.…”
Section: Discussionmentioning
confidence: 99%
“…This cross-sectional data analysis is limited due to the lack of inclusion of training characteristics,44 previous experience,45 anthropometric characteristics,42 aspects of equipment,43 and influence of weather and environmental conditions in the analysis 12,53. Some athletes might have participated in the race several times across different years, and the inclusion of repeated athletes might have had an influence on the statistical analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the traditional endurance sports running,16 cycling,1518 and swimming,11–14 new sports disciplines were created in the last two decades, such as long-distance inline skating 4245. In the early 1990s, the popularity of inline skating showed an enormous increase, leading to inline-speed skating competitions, like sprint races or marathon races such as the Athens-2-Atlanta (86 miles = 138.4 km) 46.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations